Diseño de un sistema de costos de producción para la empresa la dorada ubicada en la provincia de Sucumbíos, cantón Lago Agrio, parroquia Nueva Loja, durante el segundo trimestre del 2022 - Albán Zambrano, Anthony Joel (2022)
The present research work entitled design of a production cost system for the company La Dorada located in the Province of Sucumbíos, Lago Agrio Canton, Nueva Loja Parish, during the second quarter of 2022, was developed with the purpose of improving the control in the productive processes during the elaboration of the panela since the main problem is that the company does not have a system of costs for the production process, which has led to not knowing its real manufacturing costs and therefore its profitability, for this The main objective was to design a production cost system that will contribute to the improvement of the company during its decision making. A process cost system is of great help in industrial companies, whose production is continuous, in addition to maintaining several processes for the transformation of the raw material until the finished product is obtained and that allows identifying the total and unit cost of the product, identifying a profitability analysis that will allow knowing the percentage of profit in relation to the cost of production and cost of sale.